2007
DOI: 10.1097/01.ccm.0000287589.16724.b2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients undergoing prolonged mechanical ventilation after critical illness*

Abstract: The majority of patients requiring prolonged mechanical ventilation in a respiratory unit after acute critical illness are liberated from mechanical ventilation, survive, and have a steady improvement in the activity of daily living during the first 6 months after discharge. However, a substantial fraction of these patients does not wean from mechanical ventilation and dies from consensual withdrawal of life support after a prolonged and costly hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 28 publications
(47 reference statements)
5
70
1
4
Order By: Relevance
“…Indeed, it is our policy to treat all patients with a COPD exacerbation with respiratory failure and a pH Ͼ 7.25 in the respiratory ward. 30 Only a small proportion of our patients were discharged to home from the RICU, in line with data reported by Bigatello et al, 19 who reported that only 2% of their patients were discharged to home.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, it is our policy to treat all patients with a COPD exacerbation with respiratory failure and a pH Ͼ 7.25 in the respiratory ward. 30 Only a small proportion of our patients were discharged to home from the RICU, in line with data reported by Bigatello et al, 19 who reported that only 2% of their patients were discharged to home.…”
Section: Discussionsupporting
confidence: 78%
“…16,17 Data collected on more than 3,000 patients admitted to 5 Italian RICUs, mainly dedicated to weaning from mechanical ventilation, showed a mortality rate of about 15%, 18 which is in line with our results. Concerning a RICU located inside an acute care hospital, Bigatello et al 19 suggested that a considerable number of patients were ready to come off mechanical ventilation at the time of RICU admission, implying that in the preceding ICU stay, discontinuing mechanical ventilation had not always been a priority, and explaining the quite low mortality rate even 1 year after hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…The number of the ventilator-free days in a period of 28 days was defined by the sum of days that patients spent without an invasive airway or a noninvasive interface up to day 28 after ICU admission. Patients who had an invasive airway for o21 consecutive days where considered to have prolonged mechanical ventilation [9]. Patients were considered to have prolonged weaning when they were breathing through an invasive or noninvasive airway with ventilator assistance (pressure support ventilation, proportional assist ventilation or continuous positive airway pressure) for o7 consecutive days [10].…”
Section: Discussionmentioning
confidence: 99%
“…Weaning success is an important prognostic factor in patients requiring PMV (14,15). However, the rate of weaning success in patients requiring PMV is low, ranging from 38% to 78% (11,(16)(17)(18).…”
Section: Of MV In Differentmentioning
confidence: 99%